Kevaliditas Latihan Soal Berbasis AKM untuk Meningkatkan Literasi Numerasi pada Materi Statistika - Shela Rahmawati; Nanang Khuzaini; Monica Tita Candra Gerhana (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research is based on the low numeracy literacy skills of students, which are due to their unfamiliarity with solving numeracy literacy problems and the limited availability of such problems, making it difficult for teachers to provide numeracy literacy problems to students. Therefore, it is necessary to develop math problems that can measure students' numeracy literacy skills. The method applied in this research is Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) without implementing the fourth and fifth stages. The development process starts from the analysis stage, which includes curriculum analysis, needs analysis, and material and problem analysis. After that, in the design stage, a product prototype is designed, and in the development stage, the product is consulted with three experts as validators. Next, the product is tested on students to determine its validity and reliability. The results show that all problems have a validity coefficient greater than , which means that all developed problems fall into the valid category. The developed problems are also highly reliable, with a reliability coefficient of . Therefore, it is concluded that this development research produces 36 AKM-based problems to measure students' numeracy literacy skills in statistics that are valid and reliable.